Nurses' conceptions regarding patient safety during surgical positioning - Denilse Damasceno Trevilato; Márcia Rosa da Costa; Ana Maria Müller de Magalhães; Rita Catalina Aquino Caregnato (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To know the conceptions regarding patient safety during their surgical positioning from the perspective of nurses in a Surgical Center. Method: Qualitative descriptive exploratory study, with seven nurses from private hospital in southern Brazil in August 2018. Data generation using the Focus Group technique, with content analysis by Bardin. Results: From the data analysis, six categories emerged: "patient safety", "surgical patient risks", "nurses in the operating room", "training", "involvement of the interprofessional" team and application of the risk assessment scale. The development of injuries resulting from positioning was identified as the greatest risk for the surgical patient, highlighting the presence of the nurse in the operating room as essential for the prevention of this risk, through patient assessment and staff training. Final considerations: Nurses identified risk to patient safety in relation to surgical positioning and considered they presence in the operating room to be indispensable.